DIPLOMASI PUBLIK JEPANG TERHADAP ASIA TENGGARA PASCA KEBANGKITAN CINA - , NORIKO ADHYANTI; , Drs. Usmar Salam, MIS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
After the World War II, Japan had to deal with the consequences of being the losing party. It took a lot of efforts for Japan to gain its power back. Soft power has become very substantial since then, considering the countryâs military has been prohibited. Soft power is the ability to get something through attraction. It does not require the use of force or coercion. There are many ways to help Japan obtain soft power. One of them is public diplomacy. Japan has been engaging in public diplomacy since a long time ago, but the rising China has made the country even more serious and committed to gain its soft power through such political means. The rise of China has threatened Japanâs position in Southeast Asia, so Japanâs public diplomacy towards the region has become more important. This research is done to find out and analyze Japanâs public diplomacy towards Southeast Asia after the rise of China. There are some significant changes of Japanâs public diplomacy found in this research. The changes are the institutionalization of Japanâs public diplomacy, reforming the Japan Foundation, promoting youth, intellectual and cultural exchange, more active in international media, utilizing pop culture and promoting âCool Japanâ and last but not least, more active in disaster relief diplomacy. However, there are also some challenges found in Japanâs public diplomacy towards Southeast Asia after the rise of China, such as the dark past between Japan and Southeast Asian countries especially on World War II, the different values brought by Japanese pop culture, the unpopular two-way cultural cooperation and last but not least, the responsive public diplomacy policies which only tend to react to Chinaâs rising soft power